(untitled) (Quinto Sol, 2020)
In the last decades, the irruption of Mapuche and Pehuenche indigenous groups in the public scene of the south of the province of Mendoza (Argentina), related to specific political and cultural demands, has provoked state, academic and media debates that are far from settled. Understanding that social classifications are historical and changing ways of circumscribing alterities, the article analyzes the relational field in which identitary categories with which subordinate groups represent themselves and are represented by others are homologated, cross-linked or contrasted, according to the contexts in which they are deployed and the correlates that they demand. Based on ethnographic work in urban and rural areas of the departments of Malargüe and San Rafael, firstly, we explore the ways in which available socio-ethnic labels, political-legal recognitions of indigenous status and state sponsored spaces for the participation of Mapuche and Pehuenche representatives interact with each other. Secondly, from instruments in tension (popular and hegemonic narratives, intercultural approaches), this paper addresses the margins of choice and action enabled for actors that, positioned from a historical-cultural distinctiveness, dispute in reconfigured fields for the instrumentation of ways of life of their own.